Chemical and Antimicrobial Studies of Cupressus sempervirens L. and C. horizentalis Mill. Essential Oils: Chemical and Antimicrobial Studies of Cupressus sempervirens L. and C. horizentalis - Emami, Seyyed Ahmad; Asili, Javad; Rahimizadeh, Mohammad; Fazly-Bazzaz, Bibi Seddigheh; Hassanzadeh- Khayyat, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2006)
The essential oils of fresh fruits and terminal branches with adherent leaves of Cupressus sempervirens L. and C. horizentalis Mill., growing in Iran, were analyzed by gas chromatography-mass spectroscopy. The oils were also screened for bacteriostatic and fungistatic activities. Thirteen and ten components were identified in the essential oils of C. sempervirens and C. horizentalis, respectively. The main constituents of both fruits and leaves of C. sempervirens were a-pinene and Δ-3- carene, while they were α-pinene and Δ-2-carene for C. horizentalis. The essential oil of C. horizentalis leaves showed no antimicrobial activity against, Bacillus subtilis, Candida albicans, Escherichia coli and Staphylococcus aureus, while the essential oil of its fruits exhibited a weak effect on Bacillus subtilis. The essential oil of C. sempervirens leaves and fruits showed stronger antimicrobial activity against tested microorganisms compared to C. horizentalis essential oils. C. sempervirens fruits were relatively rich in tannins, and the leaves and fruits of C. horizentalis were quite rich in saponins and tannins. The amounts of flavonoids and alkaloids were not very high in both parts of these plants.